Ontological Cognitive Metaphor of Love in English Songs of the Late 20th Century from Cognitive Perspective - Thi Vu , Viet-Anh; Nguyen Thi Hong, Thu (International Journal of Language and Literary Studies, 2020)
The paper provides an overview of the linguistic theory relevant to cognitive metaphor and shed light into ontological metaphors of love in songs. The writer found out typical metaphorical images of love in the famous English love songs of the late 20th century from cognitive prospective. There are 86 cited sentences from 68 love songs used with 16 metaphorical expressions of three types of metaphor: structural metaphors, orientational metaphors and ontological metaphors in which ontological metaphor was focused to analyze. That how these metaphorical images are explored in the songs with the cognitive and rhetorical value can offer a new look into literary and linguistics. In addition, the writer recommends strategies in finding out, comprehending and analyzing this type of metaphor in various contexts as well as suggests some suitable ways for readers to apply metaphor in writing texts more effectively.